Features Of Literary Translation - Khamdam Ismoilov; Ergasheva, Zilola (The American Journal of Social Science and Education Innovations, 2021)
In this article, the features of translation, especially literary translation, have been considered theoretically. At the same time, the methods of approaching the translated text were briefly touched upon while showing the differences and similarities between them. Literary translation seems to be the most complex of the types of translation. Because the works of literary translation should become a factor in strengthening the interaction between peoples, enriching their culture.